UNIVERSAL Tourism enriching or degrading culture? editorial comunittee, Joop Ave, Jurgen Hillig, Koesnadi Hardja Soemantri - AVE, Joop; HILLIG, Jurgen; HARJASUMANTRI, Kusnadi (1992)
xxiv, 223 hlm ilus 23 cm